INTEGRATING HEALTH, EDUCATION, AND SPORT: THE IMPACT OF SARS-COV-2 INFECTION AND COVID-19 VACCINATION ON BREASTFEEDING, NEONATAL IMMUNITY, AND EARLY PHYSICAL DEVELOPMENT - Patrycja Kinga Marta,; Natalia Morawiecka,; Agata Ossolińska,; Magdalena Rosa-Bończak,; Gabriela Monika Ferfecka,; Klaudia Anna Pawełek,; Filip Maciej Huzarski,; Mikołaj Asztabski,; Patrycja Misiaszek,; Szymon Rydzewski, (International Journal of Innovative Technologies in Social Science, 2025)
The COVID-19 pandemic has underscored the critical role of public health education in promoting maternal and neonatal well-being. This systematic review examines the impact of SARS-CoV-2 infection and COVID-19 vaccination on breastfeeding practices, with a focus on viral transmission, the transfer of antibodies, and the broader implications for health education and early physical development. A comprehensive literature search covering studies from 2020 to 2024 was conducted. The review analyzed research on the presence ofSARS-CoV-2 in breast milk, antibody responses following natural infection and vaccination, and the subsequent effects on newborn health.The results indicate that active transmission of SARS-CoV-2 via breast milk is extremely rare, with detected viral RNA not corresponding to infectious virus particles. Importantly, breast milk from both infected and vaccinated mothers contains significant levels of IgA and IgG antibodies, which confer passive immunity to newborns. Beyond immediate nutritional and immunological benefits, breastfeeding plays a pivotal role in fostering early physical development—a foundation that may influence later engagement in sports and active lifestyles. Moreover, the excellent safety profile of COVID-19 vaccines for breastfeeding women reinforces the integration of vaccination into public health education strategies aimed at promoting comprehensive maternal and child health.These findings support the continued promotion of breastfeeding during the COVID-19 pandemic, not only for its direct health benefits but also for its broader educational and developmental impacts. The study advocates for interdisciplinary public health initiatives that integrate health education, vaccination campaigns, and the encouragement of early physical activity as essential elements in optimizing long-term health outcomes.Objective: The aim of this study is to provide an in-depth analysis of the impact of SARS-CoV-2 infection and COVID-19 vaccination on breastfeeding, with a focus on the potential transmission of the virus and the transfer of antibodies through breast milk to newborns.Materials and Methods: A systematic review of current scientific literature from 2020 to 2024 was conducted, focusing on studies examining the presence of SARS-CoV-2 in breast milk, levels of anti SARS-CoV-2 antibodies after infection and vaccination, and the clinical implications for newborn health. The search utilized a combination of keywords and logical operators such as "SARS-CoV-2, "“COVID-19, "“coronavirus, "“breastfeeding, "“lactation, "“human milk, " “transmission, "“antibodies, "“vaccination, " and”immunization." Electronic databases searched included PubMed, Scopus, Web of Science, and Embase. The review encompassed publications released from January 2020 to September 2024.Conclusions: The analysis of available data indicates that the transmission of active virus through breast milk is extremely rare and does not pose a significant risk to the newborn. Detection of viral RNA in breast milk does not equate to the presence of replication-competent virus. Additionally, studies have shown that breast milk from both SARS-CoV-2-infected and COVID-19-vaccinated mothers contains specific antibodies, predominantly IgA and IgG. These antibodies may provide passive immunity to the newborn, potentially protecting against infection or mitigating disease severity. COVID-19 vaccination in breastfeeding women has been proven safe, with no significant adverse effects observed in mothers or their infants. The findings suggest that the benefits of breastfeeding outweigh the potential risks of SARS-CoV-2 transmission. Breastfeeding is recommended both during maternal infection and after COVID-19 vaccination. The available scientific evidence supports policies promoting breastfeeding as a safe and beneficial practice in the context of the COVID-19 pandemic.